Development Programme 1967-68 Gujarat State - Planning Commission (Planning Commission, 1967)
The Annual Plan for 1966-67 which was formulated on an ad-hoc basis pending the finalisation of the Fourth Plan, envisaged a total outlay of about Rs. 50 crores. The devaluation of the rupee and the unusual stresses and strains to which the economy was subject during the year introduced a new situation and it became necessary to enforce absolute economy in expenditure and observe strict fiscal discipline. The programmes included in the Annual Plan were, therefore, reviewed with a view to assessing the extent to which the expenditure on new schemes or on new construction works could either be done away with or slowed down. As a result of this review, it was decided to effect a reduction of about Rs. 3.36 crores during the year in the original Plan outlay of about Rs. 50 crores.
Government of Gujarat, General Administration Department (Planning)